INDIA’S DEMAND FOR CRUDE OIL: PROJECTIONS TILL 2035 - Deepti Sethi; Brijesh Tiwari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Abstract*